2016
DOI: 10.1007/s10995-016-1935-y
|View full text |Cite
|
Sign up to set email alerts
|

Group Prenatal Care Results in Medicaid Savings with Better Outcomes: A Propensity Score Analysis of CenteringPregnancy Participation in South Carolina

Abstract: Objectives This study was undertaken to determine the cost savings of prevention of adverse birth outcomes for Medicaid women participating in the CenteringPregnancy group prenatal care program at a pilot program in South Carolina. Methods A retrospective five-year cohort study of Medicaid women was assessed for differences in birth outcomes among women involved in CenteringPregnancy group prenatal care (n = 1262) and those receiving individual prenatal care (n = 5066). The study outcomes examined were prematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…with further savings through pregnancy, birth, and beyond when CenteringPregnancy is associated with positive clinical outcomes. 10,11 However, many studies are subject to selection bias in that women could choose between enrolling in Center-ingPregnancy or individual prenatal care, 12 and researchers have called for better methods to assess the independent effects of the model on perinatal outcomes. 10,13 Regardless of whether health outcomes are positive or neutral, women who participate in CenteringPregnancy express high satisfaction with their care.…”
Section: Introductionmentioning
confidence: 99%
“…with further savings through pregnancy, birth, and beyond when CenteringPregnancy is associated with positive clinical outcomes. 10,11 However, many studies are subject to selection bias in that women could choose between enrolling in Center-ingPregnancy or individual prenatal care, 12 and researchers have called for better methods to assess the independent effects of the model on perinatal outcomes. 10,13 Regardless of whether health outcomes are positive or neutral, women who participate in CenteringPregnancy express high satisfaction with their care.…”
Section: Introductionmentioning
confidence: 99%
“…A recent South Carolina study of the CenteringPregnancy model demonstrated Medicaid savings as a result of reduced rates of preterm birth and neonatal intensive care unit stays. Gareau and colleagues found that there was an average savings of $22,667 in health expenditures for every premature birth prevented and an estimated return on investment of nearly $2.3 million, after a $1.7 million investment in the CenteringPregnancy model [16]. there's less likely to be a hidden agenda or a certain time."…”
Section: Impact On Health Care Costsmentioning
confidence: 99%
“…Cost-benefit modeling have been used by other investigators to demonstrate that Centering Pregnancy can be financially sustainable and possibly an income generator for outpatient clinics [20]. Moreover, a study performed in South Carolina, which used a different methodology to ours, showed savings of $2.3 million due to the implementation of group prenatal care due to a reduction of premature births and subsequent birth outcomes such as LBW and NICU visits [21]. With the aim of determining additional benefits of a program that has reduced preterm births, with the eventual reduction in health disparities, and improvement in the chances of survival and quality of life of the affected infants, we decided to calculate the costs of some of the most expensive elements associated to preterm births (NICU) and compare such costs per the differences in preterm birth rates in traditional care vs Centering Pregnancy.…”
Section: Introductionmentioning
confidence: 96%